Repercussões cardiovasculares de um treinamento multicomponente em idosos pré-frágeis - Buto, Marcele Stephanie de Souza (Universidade Federal de São Carlos, 2019)
Frailty syndrome is described as a clinical state of vulnerability to stress resulting from the decline of resilience and physiological reserves related to aging. As Frailty progresses, homeostasis maintenance become affected, as well the interactions between the physiological systems and may impair the cardiovascular control by the autonomic nervous system (ANS). Considering the multidimensionality feature of Frailty, complexity measures such as Sample entropy (SampEn) and baroreflex sensitivity (BRS) may be more adequate tools to measure these interactions in cardiovascular dynamics. For Frailty management, multicomponent interventions have been shown to be effective in physical functions, functional capacity and frailty status, mainly in intermediate stages (pre-frailty). Nonetheless, it is unclear if it would also have beneficial repercussions in cardiovascular control as well as restoring the HR complexity and BRS. Thus, this thesis is divided into two studies. The study I "Multicomponent exercise training does not improve cardiovascular control in prefrail older adults: a blinded randomized clinical study" aimed to verify if a multi-component training of 16 weeks would have effect in the cardiovascular control of prefrail older adults. The results showed that multicomponent training was not effective in improving cardiovascular control as well as in the performance of the 6-minute walk test of prefrail older adults. The study II “Multicomponent exercise training in cardiovascular complexity in prefrail older adults: a blinded randomized clinical study” aimed to evaluate the efficacy of multicomponent training in the HR complexity and BRS in prefrail older adults. The results indicated there was no improvement in the HR dynamics as complexity and baroreflex. However, individuals who did not perform the training presented a worsening (reduction) of HR complexity over time. Thus, it is suggested the maintenance of HR complexity in prefrail older adults who participated in the intervention.
Cardiovascular repercussion of a multicomponent training in Prefrail older adults
Keywords: Barorreflexo; Complexidade; Envelhecimento; Exercício físico; Fragilidade; Sistema nervoso autônomo; Baroreflex; Complexity; Aging; Physical exercise; Frailty; Autonomic nervous system; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL